Lies and deception in bacterial gene regulation: the roles of nucleic acid decoys. Issue 4 (17th April 2014) - Göpel, Yvonne; Görke, Boris
Summary Bacteria use intricately interconnected mechanisms acting at the transcriptional and post‐transcriptional level to adjust gene expression to their needs. An intriguing example found in the chitosugar utilization systems of Escherichia coli and Salmonella is uncovered in a study by Plumbridge and colleagues. Three transcription factors (TFs), a small regulatory RNA (sRNA) and a sRNA trap cooperate to set thresholds and dynamics in regulation of chitosugar utilization. Specifically, under inducing conditions a decoy site on the polycistronic chitobiose (chbBCARFG) mRNA sequesters sRNA ChiX, which represses synthesis of the separately encoded chitoporin ChiP. Base‐pairing of ChiX with its decoy has no role for the chb genes themselves when the mRNA is in excess. In the absence of substrate, however, this base‐pairing tightly represses chbC encoding a subunit of the chitosugar transporter. Thus, one and the same sRNA/mRNA interaction serves different regulatory functions under different environmental conditions. The employment of RNA decoys to control the activities of post‐transcriptional regulators themselves is an increasingly recognized mechanism in gene regulation. Another observation in the current study highlights the possibility that decoy sites might even exist on the DNA controlling the availability of TFs for their target promoters.